Sistem Informasi Pemesanan Kain Tradisonal Menggunakan Metode Agile Dengan Studi Kasus Rumah Songket Cek Unah Palembang - Akbar, Muhamad Hafiz; Saluza, Imelda; Dhamayanti (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Rumah Songket Cek Unah Palembang is a local business that sells traditional Palembang fabrics such as songket, tanjung, and jumputan. This business faces obstacles in marketing, payment, and reporting that hinder the business process. This study aims to design a website-based ordering information system using the agile method, which is flexible in accommodating changing user needs. This system is equipped with product catalog features, online ordering with payment integration via e-wallet, and structured sales reports. Data collection methods are carried out through observation, interviews, and documentation, while system testing uses the black-box testing method. This system is designed to facilitate access to product information, allow customers to order from anywhere, improve operational efficiency, expand market share, and introduce the Rumah Songket Cek Unah brand as a pioneer of original Palembang songket fabrics in the digital era. In addition, this system facilitates sales monitoring and product management through optimal feature integration.